The contemporary theatrical event. Notes on its development in Lima - Esquivel Roca, María Milagros (2021)
The article puts into focus the components of the contemporary theatrical event. To do this, it reviews several categories, such as ‘theatricality´ and ‘performance’, as well as the role of words within a scenic materiality constructed begenning with the moving body. It also examines the role of the audience as an observing translator of the meanings of the scenic event of which it partakes. This article approaches an understanding of the scenic or theatrical event through authors such as Artaud, Dubatti, Fischer-Lichte, Lehmman, Prieto and Rancière, among others. A theoretical framework is attempted for a certain theatricality that integrates any scenic manifestation in which space, sound, and body are fibers of a multi-sensory textual weave whose full meaning is wholly completed only by an active spectator.